Lockdown duration and training intensity affect sleep behavior in an international sample of 1,454 elite athletes - Romdhani, M.; Fullagar, H. H. K.; Vitale, J. A.; Nédélec, M.; Rae, D. E.; Ammar, A.; Chtourou, H.; Al Horani, R.; Saad, H. B.; Bragazzi, N. L.; Dönmez, G.; Dergaa, I.; et al. (Frontiers in Physiology, 2022)
Objective: To investigate the effect of 1) lockdown duration and 2) training intensity on sleep quality and insomnia symptoms in elite athletes.